From skillful to empathic: evaluating shifts in medical students' perceptions of surgeons through a combined patient as teacher and arts-based reflection program - Gill, Gurjot K; Ng, Stella L; Kangasjarvi , Emilia; Crukley, Jeff; Simpson, Jory S (Canadian Medical Education Journal, 2023)
Introduction: The purpose of this study was to identify whether the incorporation of a combined Patient as teacher (PAT) and arts-based reflection (ABR) program during a surgical clerkship rotation could influence more humanistic perceptions of surgeons, using an innovative evaluation approach. Methods: A novel, single question evaluation tool was created. Third year medical-students were asked to “list the top 5 attributes of a surgeon, in order of perceived importance” both before and after their surgical clerkship rotations and participation in the PAT/ABR program. Attributes identified by students were coded as either “humanistic” or “non-humanistic,” which were then analyzed using generalized linear regression models under a Bayesian framework. Results: After participation in the PAT/ABR program, the predicted probability of students ranking a humanistic characteristic as the most important attribute of a surgeon had increased by 17%, and the predicted probability of students ranking a humanistic characteristic amongst their top three attributes for a surgeon had increased by 21%. Conclusion: This innovative evaluative method suggested the success of a combined PAT/ABR program in encouraging a humanistic perspective of surgery and this approach could potentially be explored to evaluate other humanistic education initiatives.